PENERAPAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII DI SMPS TELADAN SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sari, Normila; Trisnawati, Fenny; ', Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of the problems in this study was the low student learning achievement with an average value of 63.27. This study was aims to improve student learning achievement in social studies class VIII in SMPS Exemplary Sekeladi Tanah Putih Rokan Hilir through the application of learning models Example Non Examples. This research was a classroom action research (CAR) was conducted in two cycles. Each cycle consists of two meetings and one-time delivery of content meeting the daily tests. February-March 2016, with the number of 21 students consisting of 9 men and 12 women. Classroom action research in order to succeed, the researchers set the stage that action planning, action, observation and reflection. The instrument of collecting data activity observation sheet data that teachers and students as well as achievement test. Based on the results, it can be concluded that; 1) improvement of student achievement than before action to the first cycle average of 10.47% and from the first cycle to the second cycle also increased by 8.26%, 2) completeness of increased student learning in the first cycle of 21 students, who achieve mastery amounted to 15 students with persentse 71.43% and students who did not complete six people with a percentage of 28.57%. While on the second cycle students are said to be completed 20 people or 95.24% of 21 students and students who did not complete one person or 4.76%, 3) Activities of teachers increased from 57.1% to the category enough in the first cycle of meeting first be 85.7% with good category at the confluence second cycle I. in the second cycle increased to 100% in both categories, and 4) the activity of students also increased from 36% in the first cycle to 52.4% the first meeting by category less at the second meeting of the cycle I. While the second cycle of the first meeting reached 72.8% with enough categories increased at a second meeting to be85%.Key Words: Examples Non Examples Learning Model, Students Learnig Achievement, Social Subject2